ON THE SUCCESSFUL REARING OF MACROBRACHIUM ROSENBERGII IN MEDIUM PREPARED OF COMMON SALT AND SALT PAN RESIDUE - Prakash, Shree (Indian Journal of Fisheries, 2011)
The giant freshwater prawn Macrobrachlumrosenbergii is the most importantamong fishery resources due to its large size(250 - 300 mm) and highest market price(Rs. 100 - 150/kg). The farming of thisprawn was initiated in Malaysia (Ling, 1969)and U.S.A. (Fujimura, 1972) and is nowpopularising rapidly in several Asian countries.